X-ray Crystal Structure and Theoretical Analysis of Au25-xAgx(SCH2CH2Ph)18(-) Alloy - Kumara, Chanaka; Aikens, Christine M; Dass, Amala (The journal of physical chemistry letters, 2014)
The atomic arrangement of Au and Ag atoms in Au25-xAgx(SR)18 was determined by X-ray crystallography. Ag atoms were selectively incorporated in the 12 vertices of the icosahedral core. The central atom and the metal atoms in the six [-SR-Au-SR-Au-SR-] units were exclusively gold, with 100% Au occupancy. The composition of the crystals determined by X-ray crystallography was Au18.3Ag6.7(SCH2CH2Ph)18. This composition is in reasonable agreement with the composition Au18.8Ag6.2(SCH2CH2Ph)18 measured by electrospray mass spectrometry. The structure can be described in terms of shells as Au1@Au5.3Ag6.7@6×[-SR-Au-SR-Au-SR-]. Density functional theory calculations show that the electronic structure and optical absorption spectra are sensitive to the silver atom arrangement within the nanocluster.